Encyclopedia of garden design & structure : ideas and inspiration for your garden - Fell, Derek (Firefly Books, 2005)
Presents a reference of creative gardening ideas and more than one thousand full-color captioned photographs of garden features from around the world, with alphabetical listings of design categories and tips on plant cultivation.